2012
DOI: 10.1016/j.schres.2012.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation between cerebrospinal fluid oxytocin levels and negative symptoms of male patients with schizophrenia

Abstract: Background: Accumulating evidence indicates that oxytocin plays an important role in social interactions. Previous studies also suggest altered oxytocin function in patients with schizophrenia and depression. However, few studies have examined the central oxytocin levels in these disorders. Conclusions: We obtained no evidence of altered CSF oxytocin levels in patients with schizophrenia or those with MDD. However, lower oxytocin levels may be related to higher second generation antipsychotic dose and more sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 39 publications
8
63
2
2
Order By: Relevance
“…Some evidence suggests that DA is involved in mediating some of the same maternal behaviours that are exhibited under the influence of OXT 93,94 as well as pair bonding. [95][96][97][98] Furthermore, OXT has been implicated in helping to mediate addiction and withdrawal in the mesolimbic dopaminergic pathways, 99 and differences in peripheral and central levels of OXT have been found in patients with disorders with potential DA abnormalities, such as autism, [100][101][102][103] schizophrenia [104][105][106][107][108] and social anxiety disorder. [109][110][111][112] In addition, preclinical studies have shown that dopaminergic fibres may regulate OXT release 113,114 and that the receptor binding sites and neuronal fibres of both of these neurochemicals reside in the same regions of the central nervous system and are often next to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that DA is involved in mediating some of the same maternal behaviours that are exhibited under the influence of OXT 93,94 as well as pair bonding. [95][96][97][98] Furthermore, OXT has been implicated in helping to mediate addiction and withdrawal in the mesolimbic dopaminergic pathways, 99 and differences in peripheral and central levels of OXT have been found in patients with disorders with potential DA abnormalities, such as autism, [100][101][102][103] schizophrenia [104][105][106][107][108] and social anxiety disorder. [109][110][111][112] In addition, preclinical studies have shown that dopaminergic fibres may regulate OXT release 113,114 and that the receptor binding sites and neuronal fibres of both of these neurochemicals reside in the same regions of the central nervous system and are often next to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin promotes social play in domestic dogs and the appropriate use of human social cues [Oliva et al, 2015;Romero et al, 2015]. A positive correlation between SZ progression and oxytocin levels in the central nervous system has been observed [Beckmann et al, 1985], and it is plausibly explained by a decreased sensitivity to the hormone [Glovinsky et al, 1994;Sasayama et al, 2012;Strauss et al, 2015]. Treatment with oxytocin indeed improves the performance of verbal memory learning tasks in SZ patients [Feifel et al, 2012], and attenuates the negative symptoms of the disease [Feifel et al, 2010;Modabbernia et al, 2013;Davis et al, 2014;Gibson et al, 2014].…”
Section: Behavioral Traits and Neuroendocrine Impairmentmentioning
confidence: 96%
“…Oxytocin is thought to regulate central dopamine, and might therefore exhibit antipsychotic effects (Feifel, 2011). Several studies suggest that higher plasma oxytocin levels in patients with schizophrenia correlate with fewer psychotic symptoms (Sasayama et al, 2012;Cochran et al, 2014), improved cognition (Frost et al, 2014) and pro-social behavior (Rubin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%